Euthanasia: trends and opinions in Spain - I Bernal-Carcelén (Sociedad Española de Sanidad Penitenciaria, 2020)
Abstract Objective: Analyse the evolution of opinions about euthanasia by the general public and clinical physicians from 1995 to 2019 and their influence at the present time. Material and method: Bibliographical review based on relevance and quality of publications in open access and academic access platforms. Main surveys review of public and private institutions. Congress and Senate Official Journal Sessions. Results: Recent surveys show that clinicians support the regulation of euthanasia. This position matches the general public's belief, which has grown steadily in recent decades. Discussion: Social and clinical support for the regulation of euthanasia has been fundamental. In the last two decades political parties have changed their positions, thus creating a window of opportunity.